Thermal-mechanical fatigue simulation of a P91 steel in a temperature range of 400–600°C - Saad, A.A.; Hyde, Christopher J.; Sun, Wei; Hyde, T.H. (Taylor & Francis, 2011)
This paper deals with the identification of material constants to simulate the effect of cyclic mechanical loading and temperatures. A Chaboche viscoplasticity model was used in this study to model the thermal-mechanical behaviour of a P91 martensitic steel. A fully-reversed cyclic mechanical testing programme was conducted isothermally between 400 and 600°C with a strain amplitude of 0.5%, to identify the model constants using a thermo-mechanical fatigue (TMF) test machine. Thermo-mechanical tests of P91 steel were conducted for two temperature ranges of 400 – 500°C and 400 – 600°C. From the test results, it can be seen that the P91 steel exhibits cyclic softening throughout the life of the specimens, for both isothermal and thermal-mechanical loading and this effect can be modelled by the set of viscoplasticity constants obtained. Finite element simulations of the test specimens show good comparison to isothermal and TMF experimental data.